Cochlicopa nitens (Gallenstein, 1848), a land snail (Mollusca, Gastropoda) new to Finland - Ormio, Hannu; Kakko, Iiro; Koivunen, Anne; Liukko, Ulla-Maija (Memoranda Societatis pro Fauna et Flora Fennica, 2016)
The first records of the land snail Cochlicopa nitens (Gallenstein, 1848) in Finland are presented. In the years 2011 and 2015 totally 26 specimens were found in Jomala municipality, Åland Island, southwestern archipelago of Finland (WGS84 lat: 60° 10.266΄ lon: 19° 51.092΄). The only known population is living on a small calcareous fen. Data about accompanying molluscs are also given. Among them there are two species listed in the 2010 Red List of Finnish Species: Vertigo geyeri (NT) and Aplexa hypnorum (DD). The category of Vertigo lilljeborgi is in Finland LC, but in the European Red List it is near threatened (NT).